2009
DOI: 10.1253/circj.cj-09-0204
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, EUK-8, Prevents Murine Dilated Cardiomyopathy

Abstract: Background: Mice lacking manganese-superoxide dismutase (Mn-SOD) activity exhibit the typical pathology of dilated cardiomyopathy (DCM). In the present study, presymptomatic and symptomatic mutant mice were treated with the SOD/catalase mimetic, EUK-8. Methods and Results: Presymptomatic heart/muscle-specific Mn-SOD-deficient mice (H/M-Sod2 −/− ) were treated with EUK-8 (30 mg · kg -1 · day -1 ) for 4 weeks, and then cardiac function and the reactive oxygen species (ROS) production in their heart mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Mitochondrial targeting with peptide mimetics or lipophilic cationic agents (MitoQ, SkQ1) or manganese superoxide (SOD2) mimetics (Pucheu et al, 1996;van Empel et al, 2006;Kawakami et al, 2009;Iranzo, 2011) may also offer therapy for mitochondrial antioxidant protection. However, strategies to direct these compounds to the organ or cell type of interest at the apposite time are lacking, and their impact on the redoxregulation of mitochondrial biogenesis is unknown.…”
Section: Other Compounds That Protect Mitochondria Through Mitochomentioning
confidence: 99%
“…Mitochondrial targeting with peptide mimetics or lipophilic cationic agents (MitoQ, SkQ1) or manganese superoxide (SOD2) mimetics (Pucheu et al, 1996;van Empel et al, 2006;Kawakami et al, 2009;Iranzo, 2011) may also offer therapy for mitochondrial antioxidant protection. However, strategies to direct these compounds to the organ or cell type of interest at the apposite time are lacking, and their impact on the redoxregulation of mitochondrial biogenesis is unknown.…”
Section: Other Compounds That Protect Mitochondria Through Mitochomentioning
confidence: 99%
“…The results are expressed as pmol H2O2 /min/mg protein. 9 To evaluate the in situ expression of ROS, fluorescent dihydroethydium (DHE, 10 μmol/L; Sigma) staining and 5-(and 6-)chloromethyl-2', 7'-dichlorodihydrofluorescein diacetate, acetyl ester (DCF-DA, 10 μmol/L; Molecular Probes, Eugene, OR, USA) staining were performed. The specificity of DHE and DCF-DA signals for O2 .…”
Section: Expression Of O2 -And H2o2 In the Myocardiummentioning
confidence: 99%
“…8 They exhibit a 12.3-fold larger fibrotic area and a decreased expression of connexin 43 in their myocardium in comparison with age-matched wild-type (WT) mice. 9 In contrast, heterozygous heart/muscle-specific manganese superoxide-deficient (H/M-Sod2 +/-) mice exhibit no obvious difference in phenotypes in comparison with WT mice under normal circumstances, but exhibit an excessive response to hyperoxidative conditions, such as reperfusion injury. 10 However, the arrhythmogenicity of the response to the hyperoxidative state in these mice is unclear.…”
Section: Expression Of O2 -And H2o2 In the Myocardiummentioning
confidence: 99%
“…3 Previous studies have shown that EUK-8 prevents IR injury 4 and post-ischemic reperfusion arrythmias, 5 attenuates pathologic hypertrophic growth, 6 and ameliorates pressure-overload-induced heart failure. 7 In the present issue of the Journal, Kawakami et al 8 demonstrate that EUK-8 blunts the development of dilated cardiomyopathy (DCM), and also potently reverses established DCM in the hearts of muscle-specific SOD2 knockout (H/M-Sod2 −/− ) mice. In this transgenic mouse, the lack of cardiac mitochondrial SOD activity induces excessive generation of mitochondrial ROS, resulting in the accumulation of oxidative macromolecular damage, including oxidative damage to nuclear DNA.…”
Section: Article P 2125mentioning
confidence: 92%